Factores que incide en el uso de las plataforma virtuales en los estudiantes de la Unidad Educativa Aurora Estrada y Ayala de Ramírez Pérez del cantón Babahoyo Provincia Los Ríos periodo académico 2020 - 2021 - Ilbay Chinlli, Cristhian Javier (2021)
The present investigative work has been carried out on the use of virtual platforms, in the educational unit “Aurora Estrada y Ayala de Ramírez Pérez. Today, there is no doubt that virtual platforms allow the exploration of strategies, pedagogical and technological resources used by teachers, during the preventive confinement and suspension of educational establishments in the face of the global health emergency situation due to COVID-19. This research was carried out with a quantitative methodological design of a correlational descriptive type and survey, 60 students and 5 teachers participated in the study, representing the Aurora Estrada and Ayala de Ramírez Pérez Educational Unit. The case study evidenced the existing gaps in the use of digital pedagogical technologies and resources. These differences are manifested in the educational level, the socioeconomic situation of the students, the academic performance and the help from the student's family. With these conclusions, an alternative proposal in virtual teaching is proposed, seeking how to improve, to provide a better learning experience, and most importantly, to achieve the student's goal.